Amphoteric behavior of Dy3+ in Na0.5Bi0.5TiO3: Neutron diffraction and Raman studies. Issue 9 (1st May 2021) - Behara, Santosh; Ikeda, Kazutaka; Thomas, Tiju
Abstract: We report structural and optical properties of Dy 3+ doped Na0.5 Bi0.5 TiO3 (NBT), labeled as Dyx :NBT (x = 0.00–0.14). X-ray and neutron diffraction results of Dyx :NBT (x = 0.06 and 0.08) show the occupation of Dy 3+ in both Bi and Ti-sites. Such behavior of a dopant ion occupying both in A and B-sites of ABO3 is called " amphotericity ". In conjunction with the above, Raman spectra show additional breathing vibrational (A1g ) modes in the region of 700–900 cm −1 . It confirms the asymmetry in TiO6 polyhedra and random distribution of Dy 3+ and Ti 4+ ions. Photoluminescence (PL) spectra show blue (484 nm; 4 F9/2 → 6 H15/2 ; magnetic dipole (MD) transition) and yellow (575 nm; 4 F9/2 → 6 H13/2 ; electric dipole (ED) transition) emissions. The asymmetric ratio (ED/MD) of emission transitions further confirms the amphoteric distribution of Dy 3+ ions. Amphotericity and site-dependent luminescence variation show a strong correlation in structure-property relationships. Graphical abstract: Image 1 Highlights: Amphoteric behavior of Dy 3+ ions in NBT's structure is explained. Neutron diffraction confirms the occupation of Dy 3+ ions in both Bi and Ti-sites. Multiple A1g breathing modes represent the random distribution of Dy 3+ and Ti 4+ ions. Asymmetric ratio shows the crystal field around amphoteric Dy 3+ ion is symmetrical. All the phosphors show yellowish-white emission and good CCT values.